Addressing Economic Abuse in Intimate-partner Violence Interventions: A Bacchian Analysis of Responsibility - Byrt, Adrienne (Journal of family violence, 2025)
PurposeBurgeoning research on intimate partner perpetrated economic abuse highlights the devastating and lasting impacts of economic exploitation, economic control, and employment sabotage, most often endured by women. Despite recognition of the potential outcomes that can result from intimate partner perpetrated economic abuse, such as lifelong poverty, and housing and employment insecurity, there is a dearth of evidence on prevention interventions into economic abuse, and interventions to help women recover from such abuse. This exploratory qualitative meta-synthesis examines existing research to identify key areas for systemic intervention into prevention of economic abuse.MethodsDrawing on Bacchi’s ‘What’s the problem represented to be?’ approach, this qualitative meta-synthesis analyses ‘problem representations’ in 11 studies that report on interventions into intimate partner violence, including economic abuse. Articles were identified through a systematic literature search in EBSCOhost and SCOPUS using the following search terms: ‘financial abuse’ OR ‘economic abuse’ AND ‘prevention’ OR ‘intervention’ OR ‘crisis.’ The inclusion criteria were that the study must report: (1) empirical data from an intervention; (2) focus, at least in part, on EA given such abuse is often reported alongside other forms of abuse; (3) abuse occurring within the context of a current or former intimate partner relationship.ResultsWe found that across the reviewed studies, economic abuse was not often explicitly defined, and within descriptions of tactics that constitute economic abuse, the perpetrator remained largely invisible. Interventions into intimate partner violence tended to focus on individualistic prevention/intervention through psychoeducation, men’s intervention programs, clinical interventions, women’s economic empowerment. Relational economic empowerment was also recommended alongside gender-based training to motivate couples to recognise traditional gender power dynamics in relationships.ConclusionsWe argue that most interventions individualise the prevention of and recovery from economic abuse, promoting women’s self-improvement through financial literacy, economic empowerment, and education as responses to economic violence, rather than making male perpetrators accountable for the harm they cause. This gap in existing interventions reveals an opportunity for financial and government institutions to act through transformative structural reform that disrupts – rather than responds to – male perpetration of economic abuse.